2021
DOI: 10.46654/ijresd.1503
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Perceived Leadership Style and Organizational Commitment on Job Satisfaction Among Non-Teaching Employees of Federal Universities in South-East Nigeria

Abstract: The study examined effects of perceived leadership style and organizational commitment on job satisfaction among non-teaching employees of federal universities in South-East Nigeria. Participants in the study were eight hundred and eighty-four non-teaching employees who were randomly selected from three federal universities in South-East Nigeria. The participants were made up of 323 (36.5%) males and 561 (63.5%) females with age range 22 years to 60 years, mean 35.04 years and standard deviation 9.96. The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…On the positive results, findings revealed the positive association of laissez-faire style to other factors, most especially the commitment of individuals in an organization (Amini et al, 2019;Dim & Nzube, 2020;Harb et al, 2020;Lanier, 2020). On the contrary, various findings revealed that there is a negative association between laissez-faire to commitment (Ekpenyong, 2020;Maroof Khan, 2021;Nweke et al, 2021;Robert & Vandenberghe, 2021). In summary, it can be construed that there are already previously conducted studies that have supported this study's findings.…”
Section: Laissez-faire Leadership Style and Commitmentsupporting
confidence: 39%
“…On the positive results, findings revealed the positive association of laissez-faire style to other factors, most especially the commitment of individuals in an organization (Amini et al, 2019;Dim & Nzube, 2020;Harb et al, 2020;Lanier, 2020). On the contrary, various findings revealed that there is a negative association between laissez-faire to commitment (Ekpenyong, 2020;Maroof Khan, 2021;Nweke et al, 2021;Robert & Vandenberghe, 2021). In summary, it can be construed that there are already previously conducted studies that have supported this study's findings.…”
Section: Laissez-faire Leadership Style and Commitmentsupporting
confidence: 39%
“…Perceived leadership style is an employee's cognitive feeling or perception of management style or mode of presiding over, controlling, supervising, directing, and motivating employees toward achieving organisational goals (Nweke, Okoye & Dike-Aghanya, 2021). Within the context of this study, it is an assessment or evaluation made by employees on whether their organisation's leadership is exhibiting transactional, transformational or laissez-faire leadership style.…”
Section: Concept Of Perceived Leadership Stylementioning
confidence: 99%